Belowground Ecology of Scarabs Feeding on Grass Roots: Current Knowledge and Future Directions for Management in Australasia - Frew, Adam; Barnett, Kirk; Nielsen, Uffe N.; Riegler, Markus; Johnson, Scott N. (Frontiers in Plant Science, 2016)
Many scarab beetles spend the majority of their lives belowground as larvae, feeding on grass roots. Many of these larvae are significant pests, causing damage to crops and grasslands. Damage by larvae of the greyback cane beetle (Dermolepida albohirtum), for example, can cause financial losses of up to AU$40 million annually to the Australian sugarcane industry. We review the ecology of some scarab larvae in Australasia, focusing on three subfamilies; Dynastinae, Rutelinae and Melolonthinae, containing key pest species. Although considerable research on the control of some scarab pests has been carried out in Australasia, for some species, the basic biology and ecology remains largely unexplored. We synthesize what is known about these scarab larvae and outline key knowledge gaps to highlights future research directions with a view to improve pest management. We do this by presenting an overview of the scarab larval host plants and feeding behavior; the impacts of abiotic (temperature, moisture and fertilization) and biotic (pathogens, natural enemies and microbial symbionts) factors on scarab larvae and conclude with how abiotic and biotic factors can be applied in agriculture for improved pest management, suggesting future research directions. Several host plant microbial symbionts, such as arbuscular mycorrhizal fungi and endophytes, can improve plant tolerance to scarabs and reduce larval performance, which have shown promise for use in pest management. In addition to this, several microbial scarab pathogens have been isolated for commercial use in pest management with particularly promising results. The entomopathogenic fungus Metarhizium anisopliae caused a 50% reduction in cane beetle larvae while natural enemies such as entomopathogenic nematodes have also shown potential as a biocontrol. Continued research should focus on filling the gaps in the knowledge of the basic ecology and feeding behavior of scarab larval species within Australasia. This should include host plant preferences and behavioral cues which could be utilized in pest management, for example, in trap crops. The direction of future research in biocontrol strategies should focus on identifying naturally occurring, locally adapted pathogens, if they are to achieve high efficacy in the field.